Housewives as Agents of Religious Moderation: A Maslahah Mursalah Perspective on Interfaith Family Harmony in Indonesia - Nurdin, Zurifah; Agusten, Agusten; Marfuah, Siti; Dewi, Desy Eka Citra; Puspitasari, Rini; Suryani (al-'adalah, 2025)
Interfaith families are often seen as vulnerable to value and belief conflicts. Yet, some build harmonious, tolerant relationships. This study analyzes the role of housewives as agents of religious moderation in interfaith family harmony in Bengkulu Province through the lens of maslahah mursalah. Using case studies, qualitative data were collected from in-depth interviews, observations, and focus group discussions with housewives across Bengkulu. Findings show that housewives negotiate belief differences in daily life—managing food in line with Muslim sharia, facilitating religious obligations, and fostering values such as tolerance, compassion, and respect. These actions exemplify maslahah’s principles: protection of religion (hifdz al-dīn), reason (hifdz al-‘aql), and offspring (hifdz al-nasl), within modern families. The study confirms that housewives’ religious moderation significantly boosts interfaith family harmony and enhances discourse on religion, family, and social ethics in pluralistic societies